A novel ELISA for quantification of glycoprotein in human rabies vaccines using a clinically proven virus neutralizing human monoclonal antibody - Sunil Gairola; Manish Gautam; Satish Waghmare (Taylor & Francis Group, 2020)
Global efforts on the replacement of the in vivo rabies vaccine potency test (NIH method) with in vitro methods for quantification of immunodominant glycoprotein (GP) in rabies vaccine have made significant progress. We report here, a sandwich ELISA method based on the use of a neutralizing rabies GP site III directed human monoclonal antibody (RAB-1) and a polyclonal GP specific antibody recognizing the intact form of viral GP. The method was shown to be robust, specific, linear, precise and accurate in the quantification of intact GP in vaccine samples. The assay was able to differentiate between potent and sub-potent vaccine samples. The assay was shown to be linear over the range of 0.07-2.25 IU/mL with LOD and LLOQ values of 0.035 and 0.070 IU/mL, respectively. The assay was able to quantify the GP content of rabies vaccines derived from rabies vaccine strains, e.g., Pittman-Moore, Pasteur and Flury LEP with acceptable precision (CV < 20%) and also showed good agreement with NIH potency estimates. The binding kinetics of RAB-1 with intact and modified vaccine samples were also characterized using biolayer interferometry (BLI). The developed method may be used as an alternative to the NIH method in quality control testing of human rabies vaccines.